Evaluation of bearing capacity of PHC pipe piles via the dynamic and static loading test - Li, Caihua; Li, Xuepeng (Frontiers in Earth Science, 2023)
Due to its faster implementation and potential cost savings for estimating the bearing capacity of PHC pipe piles, the High Strain Dynamic Test (HSDT) offers an alternative approach to Static Load Test (SLT). The report presents a bearing capacity study via those methods with a sliding micrometer. And a Pile Driving Analyzer (PDA) imported from the United States is employed, to determine the design parameters of pile foundation engineering and provide the error sources of bearing capacity. Sliding micrometers with cone-shaped rings are embedded in the inner side of the pile piles every 1 m for measuring the strain. The law of stress and strain at various depths during loading is presented in this paper. As a new concept, the “inflection point” is proposed by the relationship between shaft resistance and relative displacement of pile-soil. By comparing the SLT and HSDT, the relationship between toe resistance and settlement of pile is demonstrated. This paper analyses the reliability and precision, and explore the error source so as to provide theoretical evidence for trail-pile testing in future. And the error of bearing capacity between SLT and HSDT with CAPWAP studies shows that the HSDT could provide adequate results for assessing the bearing capacity of PHC pipe piles.